If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18 + -2a = -9(5a + -4) Reorder the terms: -18 + -2a = -9(-4 + 5a) -18 + -2a = (-4 * -9 + 5a * -9) -18 + -2a = (36 + -45a) Solving -18 + -2a = 36 + -45a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '45a' to each side of the equation. -18 + -2a + 45a = 36 + -45a + 45a Combine like terms: -2a + 45a = 43a -18 + 43a = 36 + -45a + 45a Combine like terms: -45a + 45a = 0 -18 + 43a = 36 + 0 -18 + 43a = 36 Add '18' to each side of the equation. -18 + 18 + 43a = 36 + 18 Combine like terms: -18 + 18 = 0 0 + 43a = 36 + 18 43a = 36 + 18 Combine like terms: 36 + 18 = 54 43a = 54 Divide each side by '43'. a = 1.255813953 Simplifying a = 1.255813953
| 21r=0 | | 12=3x+4*-9 | | -2(8-6r)=36-r | | 78-x=5x | | 1+7x=5+8x | | -5m+20=5(-4m+4) | | 6=-6(a-6)+3(a-5) | | 9=5x-2x | | 4v+5v=18 | | 4(-6x-3)=39-7x | | -9z+8+5=17 | | X^2-2=73 | | 7(1+7a)=a+7 | | -6x-6=6x+6 | | 3(1-8s)=-27 | | 2(4x-2)=3x+6 | | -7(x+8)=-84 | | 159+x+9=12x+7 | | 8x+26=6(-2x-6)+2 | | N-13=-18 | | -3(1-7n)=-31-7n | | 25*(5)525-66=5 | | -6(6r+3)+5(r+5)=69 | | 5x+18=6x+14 | | x+132=125 | | 6(2+6k)-8=-176 | | -(b-5)=b-3 | | -3(-2+x)=-10 | | -11+a=-2(7a-2) | | 19r=-57 | | x^2+(1-i)x-i=0 | | -4v+2(-1-6v)=-130 |